A Cross Sectional Study to Evaluate the Prevalence, Risk Factors and Comorbidities of Allergic Rhinitis among School Going Children (Indian Journal of Public Health Research & Development, 2023)
Background: Allergic rhinitis is a common disease affecting children and adults all over the world. The prevalenceof allergic rhinitis has significantly increased among children in developing countries. It has a significant effecton the quality of life and performance of children. There are only a few studies in India on the prevalence ofallergic rhinitis.This was a hospital based cross sectional study aimed to determine the prevalence, risk factors andassociated co -morbidities among school going children.Methods: This was a hospital based observational cross-sectional study conducted in a tertiary care medicalcollege hospital of Kerala for a period of one year. A questionnaire was distributed to 200 parents of children aged3 to 15 years attending the out-patient department. The questionnaire was prepared based on the one developedby ISSAC Steering committee (International Study of Asthma and allergies in childhood) with some additionalquestions. Questions regarding the symptoms, risk factors and co morbidities were asked and the responses wereanalyzed.Conclusion: In our study we found a high prevalence of allergic rhinitis among children. Moderate - severepersistent was the most commontype. It was associated with various co- morbidities
Keywords: Allergic rhinitis, children, asthma,prevalence, risk factors